2020
DOI: 10.3390/biom10020218
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Jackfruit365™ Green Jackfruit Flour Fortified Diet on Pegfilgrastim to Prevent Chemotherapy-Induced Leukopenia, Irrespective of Tumor Type or Drugs Used—A Retrospective Study

Abstract: Chemotherapy-Induced Leukopenia (CIL) is associated with increased mortality and economic burden on patients. This study was conducted to evaluate whether inclusion of green jackfruit flour in regular diet of those patients receiving chemotherapy, could prevent CIL. This was a retrospective study conducted among a group of patients undergoing chemotherapy for solid tumors at Renai Medicity Hospital, Palarivattom, Cochin, Kerala, India, since June 2018. The study group comprised of 50 consecutive subjects, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Chemotherapy is currently the main treatment modality for cancer. However, CIL is the most common adverse effect of chemotherapy, which is directly associated with survival rates ( Liu et al, 2013 ; Campos et al, 2015 ; Wyatt et al, 2015 ; Varughese et al, 2020 ). G-CSF is commonly used to relieve side effects and improve the QOL of patients with CIL ( Disis, 2005 ; Ohnaka et al, 2013 ; Cornes et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is currently the main treatment modality for cancer. However, CIL is the most common adverse effect of chemotherapy, which is directly associated with survival rates ( Liu et al, 2013 ; Campos et al, 2015 ; Wyatt et al, 2015 ; Varughese et al, 2020 ). G-CSF is commonly used to relieve side effects and improve the QOL of patients with CIL ( Disis, 2005 ; Ohnaka et al, 2013 ; Cornes et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ltd. These mice were housed in compliance with previously established protocols [22] within the animal facility managed by the Centre for Experimental Pharmacology and Toxicology, JSS AHER. The mice were maintained under controlled environmental conditions, including a 12-hour light-dark cycle and temperatures ranging between 21 and 24 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In most cancers, post-chemotherapy-induced leukopenia (CIL) significantly contributes to the higher mortality rates among patients. In their retrospective pilot study, Varughese et al [ 7 ] indicated that a diet inclusive of green jackfruit flour, ‘Jackfruit365 (JF365)’, significantly reduced CIL in cancer patients who were also treated with pegfilgrastim. This study should pave the way for further in-depth investigations to identify the active component for this CIL-suppressing effect of JF365.…”
mentioning
confidence: 99%